Self-efficacy and relapsed addiction tendency : an empirical study - Ibrahim, Fauziah; Kumar, Naresh; Abu Samah, Bahaman (Medwell Journals, 2011)
The former drug addicts’ abilities to overcome all obstacle in life while achieving life that is free from drugs would be influenced by self-efficacy. It means that the more a former addicts is assures of himself and his future, the wider his opportunity to succeed in recovering from drugs’ effect. On that note, this research was done to identify the level of self-efficacy amongst relapsed addicts and to identify the relationships between addicts self-efficacy and relapsed addiction tendencies. Data collected were analyzed using SPSS for windows. The sample consisted of 400 drug addicts on relapse cases which were selected through the stratified random sampling and systematic random sampling method from eight Narcotic Rehabilitation Centers (NRC) throughout Peninsular, Malaysia. This research was conducted using quantitative cross-sectional survey design. The level of addicts’ self-efficacy were measured using General Efficacy Scale (GES) with strong reliability rate at 856. The date gathered was analyzed using Pearson correlation analysis and descriptive tests. The results showed 86.3% respondents showed moderate self efficacy level to low. The results from Pearson correlation tests found that there is negative, strong and significant relationship between self-efficacy ( r = -0.790; p<0.05) with relapsed addiction. These results gave the impression that low self-efficacy factor can give negative effect to the addicts in order for them to continue to be free from drugs, especially when they facing life challenges and their surroundings after they were released from drug rehabilitation centers.